The collapse of the Spanish Republic, 1933-1936 : origins of the Civil War - Payne, Stanley G. (Yale University Press, 2006)
This history focuses on the crucial period that set the stage for the Spanish Civil War. The author details the political shifts that occurred including the 1933 election & the insurrection that followed. He examines the actions of key actors during these years & uses their own writings to challenge previous perceptions.